Do men regret prostate biopsy: Results from the PiCTure study. Issue 1 (December 2017) - Coyle, Catherine; Morgan, Eileen; Drummond, Frances; Sharp, Linda; Gavin, Anna
Abstract Background Understanding men's experience of prostate biopsy is important as the procedure is common, invasive and carries potential risks. The psychological aspects of prostate biopsy have been somewhat neglected. The aim of this study was to explore the level of regret experienced by men after prostate biopsy and identify any associated factors. Methods Men attending four clinics in Republic of Ireland and two in Northern Ireland were given a questionnaire to explore their experience of prostate biopsy. Regret was measured on a Likert scale asking men how much they agreed with the statement "It [the biopsy] is something I regret." Results Three hundred thirty-five men responded to the survey. The mean age was 63 years (SD ±7 years). Three quarters of respondents (76%) were married or co-habiting, and (75%) finished education at primary or secondary school level. For just over two thirds of men (70%) their recent biopsy represented their first ever prostate biopsy. Approximately one third of men reported a diagnosis of cancer, one third a negative biopsy result, and the remaining third did not know their result. Two thirds of men reported intermediate or high health anxiety. 5.1% of men agreed or strongly agreed that they regretted the biopsy. Conclusions Level of regret was low overall. Health anxiety was the only significant predictor of regret, with men with higher anxiety reporting higher levels of regret than men with low anxiety (OR = 3.04, 95% CI 1.58, 5.84). Men with high health anxiety may especially benefit from careful counselling before and after prostate biopsy.